2018
DOI: 10.1097/spv.0000000000000638
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ultrasound Urodynamics to Identify Differences in Bladder Shape Between Individuals With and Without Overactive Bladder

Abstract: Objectives: The objective of this study was to identify differences in bladder shape changes between individuals with overactive bladder (OAB) and unaffected individuals during ultrasound urodynamics.Methods: A prospective urodynamic study was performed with concurrent transabdominal ultrasound (ultrasound urodynamics) on individuals with and without OAB based on validated International Consultation on Incontinence Questionnaire -OAB survey scores. Three-dimensional ultrasound images were acquired at 1-minute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In this regard, many prior studies have shown that bladder shape may be important in OAB . Glass et al showed differences in bladder shape between individuals with and without OAB, and Atesci et al recently demonstrated that changes in bladder shape may contribute to lower urinary tract symptoms in men, which “may be improved if modifiable factors including increased waist circumference and loosening of the urachus are corrected”. Likewise, Habteyes et al demonstrated that during filling the wall stress of the bladder increases significantly during a load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, many prior studies have shown that bladder shape may be important in OAB . Glass et al showed differences in bladder shape between individuals with and without OAB, and Atesci et al recently demonstrated that changes in bladder shape may contribute to lower urinary tract symptoms in men, which “may be improved if modifiable factors including increased waist circumference and loosening of the urachus are corrected”. Likewise, Habteyes et al demonstrated that during filling the wall stress of the bladder increases significantly during a load.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Some of these studies have used a tablet-based sensation meter that participants used to track real-time, unprompted bladder sensation. 6,8 In addition, several previous studies have used three-dimensional (3D) ultrasound to measure bladder volume, 12 shape, 13 and biomechanics. 14 Together, the use of the sensation meter and ultrasound permits non-invasive assessments of bladder sensation and function; however, these techniques require participant training on the use of the sensation meter, and bladder sensation is potentially influenced by pressure from the ultrasound probe.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the ultrasound-measured height-to-width ratios of bladders were associated with OAB, identifying a possible shape-associated OAB subtype. [68] Unfortunately, the use of ultrasound to measure bladder wall thickness has not shown to be an effective method for evaluation of DO. [69][70] In addition to its utility in BOO, doppler ultrasound is currently being evaluated for diagnostic utility of chronic pelvic ischemia leading to DO and potentially detrusor underactivity.…”
Section: Emerging Technologies and Methods To Evaluate The Filling Phasementioning
confidence: 99%
“…[66][67] Abnormal bladder fill shape in OAB. 68 Sturm 63 , Bayat 64 , Nenadic 65 , Nagle 66 , Habteyes 67 , Glass 68…”
Section: Detrusor Biomechanical Propertiesmentioning
confidence: 99%
“… 7 Recent studies indicate that US-based bladder shape analysis may be useful for the assessment of overactive bladder (OAB). 8–10 Glass Clark et al used 3-D US imaging to quantify bladder height-to-width ratios in a group of women with OAB and a control group of age and body-mass-index-matched women without OAB. 8 They found that bladder shapes for 5/11 women with OAB were outside the 95% confidence intervals for the control group, potentially identifying an OAB subgroup with irregular bladder shapes.…”
Section: Introductionmentioning
confidence: 99%